Entre trajectoires et évènements, quand l’expertise s’attache au vivant - Dorothée Denayer (Revue d'anthropologie des connaissances)
This article offers a pragmatic look at the related progress of two scientist. The first intents to produce knowledge that is useful to the management of the savanna and the living beings it shelters. The second, a specialist in the behaviour of elephants, tries to experience them in close space and long time. Both of them are thought provoking experts in the management of the Amboseli park (Kenya) and its biological richness. Through the analysis of documents these two researchers offer (scientific articles and biographical writings), this article aims at the comprehension of their position and tries to show, how their work and the expertise they are invited to, are intermingled. And if they are in conflict, this situation should not be seen as the summary of antagonistic scientific models, but rather as the result of the multiple attachments that nurrish their knowledge and competence, sometimes complementary, sometimes contradictory.